Modelling fatty liver disease with mouse liver-derived multicellular spheroids. (November 2022) - van Os, Elise Anne; Cools, Laura; Eysackers, Nathalie; Szafranska, Karolina; Smout, Ayla; Verhulst, Stefaan; Reynaert, Hendrik; McCourt, Peter; Mannaerts, Inge; van Grunsven, Leo A.
Abstract: Chronic liver disease can lead to liver fibrosis and ultimately cirrhosis, which is a significant health burden and a major cause of death worldwide. Reliable in vitro models are lacking and thus mono-cultures of cell lines are still used to study liver disease and evaluate candidate anti-fibrotic drugs. We established functional multicellular liver spheroid (MCLS) cultures using primary mouse hepatocytes, hepatic stellate cells, liver sinusoidal endothelial cells and Kupffer cells. Cell-aggregation and spheroid formation was enhanced with 96-well U-bottom plates generating over ±700 spheroids from one mouse. Extensive characterization showed that MCLS cultures contain functional hepatocytes, quiescent stellate cells, fenestrated sinusoidal endothelium and responsive Kupffer cells that can be maintained for 17 days. MCLS cultures display a fibrotic response upon chronic exposure to acetaminophen, and present steatosis and fibrosis when challenged with free fatty acid and lipopolysaccharides, reminiscent of non-alcoholic fatty liver disease (NAFLD) stages. Treatment of MCLS cultures with potential anti-NAFLD drugs such as Elafibranor, Lanifibranor, Pioglitazone and Obeticholic acid shows that all can inhibit steatosis, but only Elafibranor and especially Lanifibranor inhibit fibrosis. Therefore, primary mouse MCLS cultures can be used to model acute and chronic liver disease and are suitable for the assessment of anti-NAFLD drugs. Graphical abstract: Image 1